Implementasi Sistem Enterprise Resource Planning Berbasis Odoo Modul Accounting dengan Metode RAD pada PT Sukamakmur Food Sukses - Luthfiana, Nuria; Sudaryanti, Dwiyani; Anwar, Siti Aminah (Universitas Islam Malang, 2024)
This study was conducted to implement the Enterprise Resource Planning software Odoo accounting module using the Rapid Application Development method in a manufacturing company that focuses on overcoming problems in the company's financial division such as inventory values, budgets, proof of expenses and receipts, journal entries to the required financial statements automatically. This research is case study research with a qualitative approach so that the data to be generated is descriptive and the analysis is carried out inductively in a medium-sized manufacturing company with data analysis in the use of the RAD method that begins with planning needs, system design, to implementation. The results obtained have been in the form of implementing an ERP system Odoo accounting module that provides solutions to problems in the company's business processes. from the results of the analysis that the ERP system is able to help companies to be able to control operational activities in just one system which has many integrated modules so as to generate financial reports that are automatically available. This research shows that the system implementation is successful in reducing several errors that cause problems and increasing effectiveness and efficiency in managing company resources.Keyword: ERP system, software ERP Odoo, RAD method, accounting, journal, budget, automated reports